DEVELOPMENT OF BATIK TULIS MODULE FOR ELEMENTARY SCHOOL TEACHER CANDIDATES - Fery Setyaningrum; Heni Siswantari; Ganing Rimas Hayu Kerti (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
This research is motivated by the difficulties of students in preparing and making written batik. So, the authors developed a complete module of written batik material for students, especially the PGSD department. This study aims to determine the steps for developing a written batik module for PGSD students and to determine the quality test by experts on the written batik module for PGSD students. The type of research that will be used is research development or Research and Development with the Borg and Gall model in Sugiyono. The types of data that will be used are quantitative data and qualitative data. The data collection technique will be carried out by the process of assessing product design by experts such as learning experts, material experts, linguists, and media experts. In addition, the authors will collect other data from the unstructured interview process as a needs analysis for UAD PGSD students, especially those who take similarity courses at UAD in the 2019/2020 academic year. The result of this research is that the development step is carried out in 5 stages according to Borh and Gall because of the limited time of the research by testing the quality of the experts' assessment of the written batik module for PGSD students, the total value of 275, 09 and the average number is 91.7. These results indicate that the written batik module for PGSD students that has been developed meets the "Very Appropriate" category.